Marine Based Natural Products: Exploring the Recent Developments in the Identification of Antimicrobial Agents. Issue 10 (16th September 2022) - Krishna M. S., Ajay; Mohan, Sangeetha; Ashitha, K. T.; Chandramouli, Manasa; Kumaran, Alaganandam; Ningaiah, Srikantamurthy; Babu, K. Suresh; Somappa, Sasidhar B.
Abstract: The marine ecosystem is the less explored, biologically diverse, and vastest resource to discover novel antimicrobial agents. In recent decades' antimicrobial drugs are losing their effectiveness due to the growing resistance among pathogens, which causes diseases to have considerable death rates across the globe. Therefore, there is a need for the discovery of new antibacterials that can reach the market. There is a gradual growth of compounds from marine sources which are entering the clinical trials. Thus, the prominence of marine natural products in the field of drug design and discovery across the academia and pharmaceutical industry is gaining attention. Herein, the present review covers nearly 200 marine based antimicrobial agents of 11 structural classes discovered from the year 2010 to 2022. All the discussed compounds have exhibited medium to high antimicrobial activity in inhibiting various microorganisms. Abstract : The review covers nearly 200 marine natural compounds across 11 structural classes discovered from 2010 to 2022. Amongst, 67 isolated bio‐actives are reported as novel structures, which exhibited high inhibiting properties.